Literasi Produk Halal Dalam Pemberitaan Media Online di Provinsi Jambi Tahun 2021 (Pendekatan Discourse Analysis) - Sofia, Rindu; Bahrum, Bahrum (Fakultas Syariah IAIN Kerinci, 2024)
Halal literacy is a person's knowledge and understanding of a product being consumed. Whether a product is halal or haram is not only seen from the halal label, understanding the halal product for someone who consumes it is also important. With the development of halal literacy in society now through online media. Meanwhile, currently there is still very little news about halal products or the halal industry in online media in Jambi that discusses halal product discourse in making news about halal products. Based on the data we obtained from news about halal products in online media in Jambi in 2021, there were only 21 news related to halal products that were published by 20 media. Grouped into 4 groups of issues in online media in Jambi in 2021, namely first, Advancing Jambi MSMEs to superior sharia products. Second, the Jambi MSME Organization encourages the birth of young entrepreneurs to become drivers or drivers of the sharia economy in Jambi. Third, Violating product guarantees aims to find out whether an item is halal or not by including a halal label and expiration date on the packaging. Fourth, the halal industry aims to become the world's leading sharia economic center. Based on data analysis, this research is qualitative research, with van Dijk's critical linguistic analysis model such as critical semiotic analysis, language, discourse, communication and other social sciences. This research analyzes the discourse on halal products, namely providing an overview and explanation, then analyzing it to draw conclusions.